Membentuk Spiritualitas Iman Di Tengah Anggota Keluarga Katolik - Anjeli Sarma; Intansakti Pius X (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
Spirituality is a spiritual conversation with the human soul. So by forming a spirituality of faith, humans can realize their identity regarding spiritual inner strength regarding their relationship with God and others. For this reason, the author raised this article because the author personally in the life of his parents and family has not experienced this spirit of faith. For example, in concrete terms, the author sees that the prayer life of the family is very lacking, the social life is not extensive enough, personally the life is still thinking about yourself, the lack of self-confidence makes the inner side easily give up, for example, there is a problem in the family and because of that problem the family doesn't want to go away. to church, this caused his spiritual life to decline. This article uses a qualitative method, namely direct observation taken from several life stories of Catholic families. For this reason, this article is intended to be a hope for Catholic families to always develop and maintain the spirituality of faith in their spiritual life.